Strategi Rekrutmen Dan Seleksi Di Era Digital Pada J&T Cargo, Dr. Sutomo, Lubuk Begalung - Aguesto Azhara; Muhammad Azima; Vivi Tri Nanda; Zilfa Aulia Marsandi; Vivi Nila Sari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The development of digital technology has brought significant changes to various aspects of company management, including human resource management. One human resource management function significantly influenced by technological advancements is the employee recruitment and selection process. Logistics companies are required to have competent, adaptable employees who are able to work with technology-based systems. This study aims to identify and analyze recruitment and selection strategies in the digital era at J&T Cargo Dr. Sutomo Padang. This research used a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation studies sourced from the company's operational activities. The results indicate that the implementation of digital-based recruitment and selection at J&T Cargo facilitates the recruitment of prospective employees, increases the efficiency of the recruitment process, and helps the company obtain a workforce that meets its needs. However, challenges remain, such as differences in employee technological adaptability, necessitating ongoing training and development.